Syari’at Perlindungan dan Pemeliharaan Alam - Ahmad Sudirman Abbas (Universitas Nasional, 2017)
This paper discusses the important aspect of the shari’a practical wisdom as exemplified by Prophet Muhammad and his companions. Protecting the environment and creatures is one of the sharia objectives, on which human being is exalted into the position of Khalifah, that suggests the role of ‘guardian’ or ‘custodian’. It means that human being can fulfill its protector duties without undermining its existential being. The custodial objective is achieved when human being is able to preserve and develop the environment, not exploit and destroy. The development in the context of ‘custody’ does not necessarily mean prohibition of using and utilizing environmental resources, instead, it is a call to meet the need with reasonable and sustainable consideration. Humans are in need of caring and passionate behavior toward others, animals, trees and plantation and even they need to plant trees for the sake of mother earth.That is why, in its applicable nature, not only did Islam recognize the existence of flora and fauna, but also treats them equal to human being. As further consequences of the aforementioned implementation of Islam, humans are supposed to behave passionately and with full of care to the whole and real world.Keywords: Khalifah, fauna-flora, environmental preservation, shari’a, sustainable utilization. Makalah ini membahas sisi penting kearifan praktis syari’at Islam yang dicontohkan oleh Nabi Muhammad SAW serta para sahabatnya. Dari ajaran syari’at dapat diketahui bahwa memelihara lingkungan serta makhluk hidup merupakan salah satu dari tujuan syariah. Oleh karena itu manusia diberi predikat khalifah dalam kelestarian alam serta isinya. Sebagai khalifah, manusia berperan sebagai ‘penjaga’ dan ‘pemelihara’. Sebagai pemelihara, ia menjalankan tugas tanpa mengurangi eksistensinya. Pemeliharaan ini tercapai manakala manusia mampu melestarikan dan mengembangkan – bukan mengurangi dan menghabiskan, bahkan menghancurkan. Pengembangan dalam kriteria ‘pemeliharaan’ tidak berarti larangan menggunakan atau memanfaatkan, tetapi justru anjuran memenuhi kebutuhan dengan pertimbangan logis dalam rangka pemanfaatan yang berkelanjutan. Dalam bahasan ini lah diperlukan perilaku berlemah lembut terhadap manusia, berbuat baik kepada binatang, pepohonan dan tumbuhan hingga anjuran untuk menanam pohon untuk kebaikan di bumi. Oleh sebab itu, syaria’at Islam tidak hanya mengakui keberadaan fauna-flora, serta makhluk lainnya, namun memposisikan mereka sama dengan manusia. Maka sebagai tindak lanjut implementasi itu, manusia hendaknya mempunyai perilaku kasih sayang dalam kehidupan yang nyata kepada seluruh alam.Kata Kunci: Khalifah, fauna-flora, memelihara alam, shari’at, pemanfaatan berkelanjutan.